2022
DOI: 10.5582/bst.2022.01019
|View full text |Cite
|
Sign up to set email alerts
|

Conversion therapy with an immune checkpoint inhibitor and an antiangiogenic drug for advanced hepatocellular carcinoma: A review

Abstract: Hepatocellular carcinoma (HCC) has been the fifth most common malignancy worldwide and is the second most common cause of tumor-related mortality globally. In China, a high proportion of patients with HCC present with an advanced stage of the disease, so HCC is a major challenge to the healthcare system and a substantial socioeconomic burden. The last decade has witnessed an expansion of the treatment landscape for HCC. Various approaches have been explored as potential conversion therapies for advanced HCC. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…The patient in our case complied with the following standards: ECOG-PS rating was zero. Second, the modified response evaluation criteria in solid tumors (mRECIST) standard was created to more accurately assess the response of liver lesions because it has advantages in determining the level of pathological response ( 22 , 23 ). Therefore, in our report, we evaluated the tumor response to therapy using mRECIST criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The patient in our case complied with the following standards: ECOG-PS rating was zero. Second, the modified response evaluation criteria in solid tumors (mRECIST) standard was created to more accurately assess the response of liver lesions because it has advantages in determining the level of pathological response ( 22 , 23 ). Therefore, in our report, we evaluated the tumor response to therapy using mRECIST criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that Targeted agents and immunotherapy combination showed good ORR in HCC, 28 and targeted agents and immunotherapy combination with hepatic artery intervention had an ORR of up to 96% and a conversion resection rate range from 12.7% to 56%. [29][30][31] Although combination therapy can greatly prolong the survival of patients with advanced HCC, surgical resection is still the treatment associated with the best long-term survival in liver cancer patients, 32,33 as well as the only radical treatment method. In 1977, Shafer proposed the concept of preoperative conversion, in which preoperative combination therapy leads to a decrease in tumor size and vascularity, thus making surgery feasible.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of advanced therapies, various emerging treatments have achieved positive results ( 19 , 20 ). However, because of the complexity of the genetic background of HCC, the benefits of these treatments remain unclear ( 20 , 21 ). Therefore, in-depth studies of the pathogenesis of HCC, including machine learning, will have clinical significance for predicting the interaction of hub genes and investgating prognostic-related molecular markers for individuals.…”
Section: Discussionmentioning
confidence: 99%